Doppler Velocimetry of the Venous Ductus. Technical Aspects - Zavala Coca, Carlos Alberto (2022)
The doppler velocimetry of venosus ductus has been used as an important tool to establish the ideal moment to interrupt high risk pregnancies associated with doppler velocimetry alteration of fetal and umbilical-placental compartments. Technical aspects of identifying DV are discussed in the present study.